2021
DOI: 10.1038/s41467-021-26989-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene editing with CRISPR-Cas12a guides possessing ribose-modified pseudoknot handles

Abstract: CRISPR-Cas12a is a leading technology for development of model organisms, therapeutics, and diagnostics. These applications could benefit from chemical modifications that stabilize or tune enzyme properties. Here we chemically modify ribonucleotides of the AsCas12a CRISPR RNA 5′ handle, a pseudoknot structure that mediates binding to Cas12a. Gene editing in human cells required retention of several native RNA residues corresponding to predicted 2′-hydroxyl contacts. Replacing these RNA residues with a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…More recently, Gagnon, Damha, and co-workers reported similar results that crRNAs optimized using a structure-guided approach and containing up to 13 2′-F nucleotides in the 5′-handle pseudoknot had activity similar to the unmodified crRNA . This study also showed that individual 2′-NH 2 modifications of the positions that tolerated the 2′-F nucleotides in the 5′-handle pseudoknot decreased the Cas12a activity.…”
Section: Modifications Of Cas12a and Cas13 Crrnasmentioning
confidence: 71%
See 1 more Smart Citation
“…More recently, Gagnon, Damha, and co-workers reported similar results that crRNAs optimized using a structure-guided approach and containing up to 13 2′-F nucleotides in the 5′-handle pseudoknot had activity similar to the unmodified crRNA . This study also showed that individual 2′-NH 2 modifications of the positions that tolerated the 2′-F nucleotides in the 5′-handle pseudoknot decreased the Cas12a activity.…”
Section: Modifications Of Cas12a and Cas13 Crrnasmentioning
confidence: 71%
“…Modification of the 5′-handle pseudoknot strongly decreased the activity in both in vitro and cellular assays . A more recent study also showed that DNA modifications were not tolerated in the 5′-handle pseudoknot of crRNA in an assay that used HEK293T cells stably expressing EGFP …”
Section: Modifications Of Cas12a and Cas13 Crrnasmentioning
confidence: 99%
“…In conjunction with UV denaturation studies, they revealed that OxT 2 and OxT 3 are suitable to be incorporated in the DNA strand of hybrid duplexes due to their favorable structural and functional features, such as dihedral angle preferences and Hbond interactions. Together, they account for a rare type of "DNA-like" modification that, on the one hand, is well accommodated inside DNA−RNA hybrids, thereby with potential applications in xenobiology, 1 and antisense 30 and CRISPR technologies, 31 and, on the other hand, expands the "toolbox" of modifications that nucleic acid chemists and biologists can experiment with.…”
Section: Scheme 4 Synthesis Of Oxepane Nucleoside Phosphoramiditesmentioning
confidence: 99%
“…R f = 0.44, hexane/EtOAc (3:2, v/v). 31 To a solution of 13 (130 mg, 0.17 mmol) in dry CH 2 Cl 2 (1 mL) were added ( i Pr) 2 NEt (92.0 μL, 0.51 mmol) and 2-cyanoethyl N,Ndiisopropylchlorophosphoramidite (114 μL, 0.51 mmol) at room temperature. The reaction mixture was stirred at 90 °C for 2 h in a microwave sealed reactor vessel tube.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation